Visual-Spatial Ability: Important in STEM, Ignored in Gifted Education - Andersen, Lori (My University, 2014)
Visual–spatial ability is a multifaceted component of intelligence that has predictive validity for future achievement in science, technology, engineering, and mathematics (STEM) occupations. Although identification and development of STEM talent is a national priority, visual–spatial ability is rarely measured and relatively neglected in gifted education. Quantitative and verbal reasoning abilities are favored over nonverbal abilities in talent searches and gifted programs, which causes some high-spatial, gifted students to be overlooked. Creative production in STEM requires visual–spatial ability, and this ability must be developed in gifted education. Theories of intelligence and testing have advanced to provide methods for identification of specific cognitive abilities, such as visual–spatial ability. However, for these students to be successful in gifted programs, gifted-education services must be modified to accommodate gifted spatial learners and develop spatial talents.
Keywords: Cognitive abilities; Creative production; Gifted education reform; Identification of giftedness; Intelligence testing; Science education; STEM talent development; Visual-spatial ability